THE IMPACT OF NANOTECHNOLOGICAL INNOVATIONS ON THE COMPETITIVENESS OF THE GLOBAL MARKET - KHALATUR, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In today's global market, the integration of nanotechnological innovations has become a crucial factor affecting competitiveness. This article explores the multifaceted impact of nanotechnology on global market dynamics, emphasising its role in improving industrial efficiency, creating new products and stimulating economic growth. The analysis emphasises that nanotechnology plays a key role in the context of the Fourth Industrial Revolution (Industry 4.0), transforming industries and creating new competitive advantages on a global scale. This article outlines the significant impact of nanotechnology innovations on the global market, highlighting the interconnection between globalisation, technoglobalisation and Industry 4.0.To provide a broader perspective on the topic, Ukraine was analysed and compared with the following countries: The United States of America, Germany, China, Japan, Israel, and Finland. These countries are interesting for comparison with Ukraine in terms of the development and implementation of nanotechnologies, as well as their impact on competitiveness in the global market. Each of these countries has its own unique achievements and strategies that can provide valuable insights for the study. Comparing Ukraine with these countries will help to identify the strengths and weaknesses of the national nanotechnology industry, as well as to identify potential areas for development and increase of Ukraine's competitiveness in the global market. Globalisation has greatly accelerated the spread of technological innovation across borders, contributing to a more interconnected and competitive global marketplace. In this context, nanotechnology, defined as the manipulation of matter at the atomic and molecular levels, has become a transformative force.This article analyses the costs of education and business in the countries studied, providing a global overview of important indicators that may affect competitiveness in the global market. The findings of this study allow us to compare the level of investment in education and infrastructure in the countries studied and their impact on competitive positions on a global scale.
Keywords: globalization; technoglobalism; technology; innovative development; nanotechnology; global market; industrial revolutions; Industry 4.0